A Rare Case of Endolymphatic Sac Tumour: Clinicopathologic Study and Surgical Management - Emanuele Ferri; Maurizio Amadori; Enrico Armato; Ida Pavon (Case Reports in Otolaryngology)
Objective. Endolymphatic sac tumor (ELST) is a rare neoplasm arising from the intrapetrous portion of the endolymphatic sac, either isolated or in association with the von Hippel-Lindau disease. We report a sporadic case of ELST with an overview of the literature and a discussion of clinic-radiological, histopathologic, and surgical findings. Case Report. A young woman presented with a progressive hearing loss in the left ear. Otoscopy showed a reddish, bleeding hypotympanic mass. CT demonstrated an expansile lytic mastoid lesion extending to the middle ear, with bone erosion. MRI confirmed a lesion of increased signal on T1-weighted sequences. The patient underwent a canal wall-down tympanoplasty with complete removal of the tumor. Histopathology was consistent with a papillary ELST. Immunohistochemistry was positive for cytokeratin and chromogranin A. Conclusion. This paper highlights the rarity of ELST, the need for an accurate neuroradiological and immunohistochemical study at the early stages, and the timeliness of surgical treatment.